THE EFFECT OF PROFITABILITY AND OTHER FACTORS ON THE VALUE OF COMPANIES IN THE APPAREL & LUXURY GOODS SUB-SECTOR - WIRANTI , JIHAN KEMALA; DEITIANA, TITA (E-Jurnal Manajemen Trisakti School of Management (TSM), 2021)
To be able to achieve proper financial management, a company must pay attention to financial decision making, these decisions will have a big impact on the company's future. One of them is in the apparel & luxury goods subsector companies, there is a lot of market competition for apparel & luxury goods companies in Indonesia which have high competitiveness with foreign apparel & luxury goods companies, plus the Covid-19 pandemic has made everyone have the power to buy quite low. This research aims to determine the effect of independent variables, namely profitability, liquidity, company size, capital structure, and TATO on the dependent variable, namely company value. By using a research method, namely causality or cause and effect between independent and dependent variables, by measuring each variable using statistical analysis techniques with 187 samples in 17 companies for 11 years. The research results show that in the profitability variable, company size, and capital structure have a positive effect on firm value, while the liquidity and TATO variables have no effect on firm value.